Some fishing methods in Lingayan Gulf. - Lucas, Reynaldo M. (College of Fisheries, University of the Philippines, 1952)
In connection with my practice in industry in Lingayan Gulf, I was able to make fiorst hand observation on the fishing gear and methods of fishing used in this region. Although I spent most of my time goingh with an otter trawler, I had the opportunities of observing the different methods of fishing used by the majority of the fishermen in this region. With the increasing demand for more fresh fish the fishermen in this region, like others, employ various methods of catching fish. Primitive methods as well as modern methods of fish capture are employed by the fishermen of this locality, Geographically, Lingayan gulf is a good groud for any kind of fishing gear, as a matter of fact, it is considered as one of the best fishing grounds in the island. The chart reveals that the bottom is smooth, thus favorable for trawling purposes. Various methods of fish capture sucjh as beach seine, gill net, handline and others are the most common of the gears being used by thios locality. Not very modern methods of fishing have done much to satisfy the demnds for fish in the civicinity. This report is designed to give some information about the mthods of fishing used, and insight into the opportunities it offers, and the perception of its problems. Moreover, I cannot refrain from expressing my immeasurable gratitude to tge instructors of the Philippine institute of fisheries technology, to the superintendent, as well as our course adviser, Mr. Santos B. Rasalan, for giving me some valuable advice. To Mr. Juanito Arciaga and Mr. Palmares of Damortis, La Union, special thanks are due fo the kindness they have shown in accommodating me in their fishing boats.